If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5r = r + 4 Reorder the terms: 5r = 4 + r Solving 5r = 4 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. 5r + -1r = 4 + r + -1r Combine like terms: 5r + -1r = 4r 4r = 4 + r + -1r Combine like terms: r + -1r = 0 4r = 4 + 0 4r = 4 Divide each side by '4'. r = 1 Simplifying r = 1
| 3y+4=-11 | | -68=4+8d | | 12x-8/3 | | 5/x=3/2 | | 0.5(-2x+7)+2.7X= | | -4/7(4t+2)=5/28t-13 | | 4x+6x-3=92 | | -5b-3=-12 | | 3d+9=(6d-4) | | 6n+7ifn=7 | | n+1/n=10/3 | | 6.6x-2.58=3.9-4.3x | | -3+5u=-8 | | 1.5(6m+6)-(m+9)= | | -(2m+1)-5(-1+3m)=-13 | | 8*6-8*2= | | 2/3(m)=10 | | 2(x+3)/x+3 | | 5y-6+y+50=7y+50-4y | | 4p-3=2q+8 | | 2n-5=3(1-2n) | | 5+5k=-6(k+6)+8 | | -3y+12=48 | | 13=w/3+7 | | -2(x+3)=9+3x | | 3-(k+1)=-2 | | 8+3x-2=9x+13-5x | | -3/8k=-12 | | b^4-49=0 | | 12.5/4 | | 9=1+7 | | -3(2k-6)-4(4k-5)-11k= |